PENGARUH BERBAGAI MACAM EMPON DAN SINBIOTIK TERHADAP PERTUMBUHAN LARVA UDANG PUTIH (Litopenaeus vannamei) - Sumardi, Sumardi; Handayani, Kusuma; Susanto, Gregorius Nugroho; Ayuandira, Niken; Prihadhi, Eka (Universitas Jambi, 2025)
The global market demand for vaname shrimp in Indonesia is increasing every year. Vannamei shrimp is a mainstay of fisheries commodities. Cultivators often encounter vibriosis disease caused by Vibrio sp. Therefore, it is necessary to pay attention to the quality of the feed by adding supplements from synbiotics and empon-empon. This study aims to determine the effect of synbiotics and empon-empon on the growth of white shrimp (Litopenaeus vannamei) larvae in controlling Vibrio sp. Parameters measured included daily length growth, survival, water quality, total bacteria, and total vibrio. Water quality and total bacteria are growth-supporting factors. The treatments consisted of positive control (C+), negative control (C-), Synbiotic 1 (S1), Synbiotic 2 (S2), Synbiotic 3 (S3), Synbiotic 4 (S4), and empon-empon (E). The synbiotics used were Bacillus sp 1x 1010. as a probiotic, 2 ppm yam paste as a prebiotic and 1 ppm ginger, 1 ppm white turmeric, and 1 ppm black cumin. And the combination of the three types of empon-empon with a concentration of 0.5 ppm (treatment S4 and E). The results showed that the S2 treatment had a significant effect (P>0.05) on the daily length of the fry with an average of 0.05±0.06 mm. The S4 treatment had a significant effect on survival with a percentage of 83.6%. The lowest total Vibrio was shown in the S4 treatment with a value of 0.45±0.5 logs CFU/ml. The total density of bacteria was shown in the S2.treatment with a value of 2.28 ±log CFU/ml.